Sunday

December 21, 2014

December 21, 2014

Posted by **Samantha** on Sunday, April 18, 2010 at 7:19pm.

3x-y=8

x-y=8

Step 1

3x-y=8

3x-y+y=8+y

3x=8+y

3x/3=8+y/3

x=(8+y/3)

Step 2

3(8+y/3)-y=8

8+y-y=8

8+2y=8

8+2y-8=8-8

2y=0

2y/2=0/2

y=0

Step 3

x=8+y(0)/3

x=2.6

- Algebra1 -
**Reiny**, Sunday, April 18, 2010 at 9:04pmWhat a hard way of doing it.

look at the second equation, it is very easy to solve for x

x = 8+y

now sub that into the first

3(8+y) - y = 8

24 + 3y - y = 8

2y = -16

y = -8

back in x = 8+y

x = 8+(-8) = 0

Your last two lines of step1 are wrong

should have been

3x/3=(8+y)/3

x=(8+y)/3

of course that makes all the statements is Step 2 incorrect.

**Answer this Question**

**Related Questions**

ALGEBRA HELP - When solving the equation, what property was used to go from step...

algebra 1 - ELEMENTARY ALGEBRA #3 Page 23 Chapter 3 Lesson 3.02 Solving Multi-...

MATH - A student is solving the equation 81x – 1 = 3x + 2. Step 1: 81x – 1 = 3x...

Quick math help - In which step below does a mistake first appear in simplifying...

Algebra help - f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this? This is...

math - Solving Equations with Fractions 1/2 x - 1/3 x = 7/3 solve for X i need ...

L Pre-Cal - Hey! I'm getting stuck on how to solve this system of linear ...

algebra - please giveme step by step instructions on how to solve linear ...

Algebra - Can you please give an example step by step of how to solve a system ...

Math - I am really have a tough time trying to solve this problem. I think my ...